Effectiveness of Transdiagnostic Treatment on Health Locus of Control and Emotional Regulation in Patients with Coronary Heart Disease - Rafei, Farnoosh; Hatami, Mohammad; Baghdassarians, Anita; Rafieipour, Amin (International Journal of Applied Behavioral Sciences, 2019)
Introduction: Coronary heart disease (CHD) is one of the main death causes in the world. Therefore, it is necessary to identify the psychological disorders in these patients and to apply the necessary interventions to reduce them. The purpose of the present research was to examine the effectiveness of transdiagnostic treatment on health locus of control and emotional regulation in patients with CHD. Methods: This research was a quasi-experimental one with the plan of pretest posttest control group. The statistical population included all patients with coronary heart disease 40-65 years old who were treated in Kasra hospital of Tehran in 2019. The sample included 90 patients assigned to the two groups experimental and control group randomly. Data were collected using the Multidimensional Health Locus of Control Scale and Emotional Regulation Scale. The data were analyzed using the methods of multivariate analysis of covariance (MANCOVA). Results: The result showed that the transdiagnostic therapy significantly increases the internal health locus of control and emotional regulation in the experimental group (p<0.01). Discussion: This finding has important implications as regards the education and mental health of patients with coronary heart disease. Based on the results, it is necessary to pay more attention to two variables health locus of control and emotional regulation in the design of interventions to reduce the psychological problems, patients with CHD. Declaration of Interest: None